Transnational maritime environmental crime and the BBNJ Agreement - Lothian, Sarah Louise (Frontiers in Conservation Science, 2024)
Marine areas beyond national jurisdiction are a prime target for transnational maritime environmental crime due to a fragmented international legal framework and a lack of coordination and cooperation between governance and institutional structures. On 19 June 2023, member States of the United Nations adopted the Agreement under the United Nations Convention on the Law of the Sea on the Conservation and Sustainable Use of Marine Biological Diversity of Areas Beyond National Jurisdiction (BBNJ Agreement). As the third Implementing Agreement to the 1982 United Nations Convention on the Law of the Sea (LOSC), the BBNJ Agreement seeks to secure the long term protection and integrated management of marine biodiversity through the effective implementation of relevant provisions of the LOSC and by strengthening and promoting cooperation and coordination between and among relevant legal instruments, frameworks and relevant global, regional, subregional and sectoral bodies. This article examines the relationship between the BBNJ Agreement and transnational maritime environmental crime and considers ways the instrument could assist in efforts to combat such crime. As part of this analysis, this article explores how the BBNJ Agreement could provide an important platform for the formation of key partnerships and alliances by means of regional and bilateral dialogues, outreach and coalition-building to address transnational maritime environmental crime and mobilize and sustain the momentum for global action on this issue.